Influence seasons of the year and somatic cell counts on physical-chemical and sensory parameters of milk and coalho cheese - Lima, Edine Roberta de; Oliveira, Juliana Paula Felipe de; Bezerra, Maria de Fátima; Borba, Luis Henrique Fernandes; Bezerra, Joadilza da Silva; Rangel, Adriano Henrique do Nascimento (Acta Scientiarum. Animal Sciences, 2019)
The objective of this study was to evaluate the influence seasons of the year and somatic cell counts (SCC) on physical-chemical and sensory parameters of cow’s milk from individual and collective refrigeration tanks with different milking systems. In addition to analyzing the sensory acceptance of pasteurized milk and coalho cheese developed with high (> 800,000 cells mL-1) and low SCC levels (<200,000 cells mL-1). Seasonality did not affect fat content, casein, lactose, total solids, defatted dry extract and SCC, but lower protein levels than May and June were observed from July to September. Based on the SCC results, milk from refrigeration tanks was classified as low SCC and high SCC. The samples were used to obtain pasteurized milk and coalho cheese which were sensorially evaluated for general appearance, odor and flavor by a panel of untrained tasters using a hedonic scale of 9 points. Pasteurized milk with high and low SCC presented pleasant sensory characteristics to the consumer up until two days of storage. The same behavior was observed for coalho cheese at 20 and 40 days of shelf life, respectively.